Volume 4: Fluid-Structure Interaction 2014
DOI: 10.1115/pvp2014-28854
|View full text |Cite
|
Sign up to set email alerts
|

Blast Adjustment Factors for Elevated Vertical Cylindrical PVBs

Abstract: Pressure vessel burst (PVB) is an explosion scenario commonly encountered at chemical processing facilities. PVBs pose both blast and fragmentation hazards. Blast prediction methods specific to PVBs were first developed in the 1970s and revised blast curves were published in 1995. The published blast curves were developed for spherical vessel bursts. However, most pressure vessels are cylindrical rather than spherical. The blast wave originating from a cylindrical PVB is not spherical (i.e., as with a spherica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The contours indicate where the designated overpressure has been reached. When the devised function is applied, the safety distance is 31.6 m. At this distance, the pipes are broken, followed by gas leakage, and the concrete wall of the spray collapses; this is comparable to the criteria of Clancey 30 and Kinney and Graham, 31 who stated that partial demolition of houses under an overpressure of 1 psi. In addition, when the function of the safety distance expands to the op cylinder = 2.5 psi line (15 m) and the op cylinder = 7 psi line (6 m), the accident result and the criteria show a united tendency, as described in Figure 6.…”
Section: Validationmentioning
confidence: 67%
See 2 more Smart Citations
“…The contours indicate where the designated overpressure has been reached. When the devised function is applied, the safety distance is 31.6 m. At this distance, the pipes are broken, followed by gas leakage, and the concrete wall of the spray collapses; this is comparable to the criteria of Clancey 30 and Kinney and Graham, 31 who stated that partial demolition of houses under an overpressure of 1 psi. In addition, when the function of the safety distance expands to the op cylinder = 2.5 psi line (15 m) and the op cylinder = 7 psi line (6 m), the accident result and the criteria show a united tendency, as described in Figure 6.…”
Section: Validationmentioning
confidence: 67%
“…Baker et al 25 found that the explosion energy should be doubled when a pressure vessel is located on the ground because of surface reflection. In addition, the PVB of a nonspherical tank has been studied 28–30 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geng et al . investigated the directional blast effects of cylindrical pressure vessel burst numerically, resulting in a group of adjustment factors for blast overpressure and impulse for a range of vessel geometries and burst conditions.…”
Section: Introductionmentioning
confidence: 99%